Association between cardiorespiratory fitness and submaximal systolic blood pressure among young adult men: a reversed J-curve pattern relationship. Issue 11 (November 2015) - Prasad, Vivek K.; Drenowatz, Clemens; Hand, Gregory A.; Lavie, Carl J.; Sui, Xuemei; Demello, Madison; Blair, Steven N.
Abstract : Objectives: Exercise blood pressure is a marker of future cardiovascular morbidity and mortality among individuals with or without high resting BP or any other cardiovascular disease (CVD) signs and symptoms at present. The purpose of this study was to evaluate the association between SBP during submaximal exercise and cardiorespiratory fitness (CRF) among young men. Further, we investigated the trend displayed by submaximal SBP (SSBP) across different levels of CRF. Methods: Graded exercise test (GXT) using a Modified Bruce protocol was performed on 204 men; SSBP was recorded at each stage of the protocol. Quintiles of CRF were established on the basis of peak oxygen consumption (VO2 ), with the first quintile (Q) being the lowest fit group and fifth Q the most fit. Results: The mean VO2 peaks in Q 1 through 5 were 32.3, 39.1, 43.4, 48.1 and 55.5 ml/kg per min, respectively. In a model adjusted for age, race, body fat percentage, resting SBP, alcohol intake and smoking, the largest difference in SSBP was observed between men in Q 1 and 2, with 7.6 mmHg ( P = 0.05), 9.4 mmHg ( P = 0.02) and 9.5 mmHg ( P = 0.04) lower SSBP at minutes 6, 8 and 10 of GXT, respectively. SSBP plateaus at Q 3, followed by an increase in the higher Qs, although still lower than Q1. Conclusion: There was a reverse J-curve pattern relationship between SSBP and CRF, with the lowest SSBP among men with fair or good CRF and highest among those with poor CRF. Video abstract: http://links.lww.com/HJH/A538 Abstract : Supplemental Digital Content is available in the text